Pediatric diffuse midline glioma H3K27- altered: A complex clinical and biological landscape behind a neatly defined tumor type - Vallero, Stefano Gabriele; Bertero, Luca; Morana, Giovanni; Sciortino, Paola; Bertin, Daniele; Mussano, Anna; Ricci, Federica Silvia; Peretta, Paola; Fagioli, Franca (Frontiers in Oncology, 2023)
The 2021 World Health Organization Classification of Tumors of the Central Nervous System, fifth edition (WHO-CNS5) has strengthened the concept of tumor grade as a combination of histologic features and molecular alterations. The WHO-CNS5 sub-category of “Pediatric-type diffuse high-grade gliomas - diffuse midline glioma, H3 K27-altered” incarnates an ideally perfect integrated diagnosis in which location, histology and genetics define clearly a specific tumor entity. It tries to uniformly characterize a group of neoplasms that occur primarily in children and in midline structures with a dismal prognosis. Such a well defined pathological categorization has strongly influenced the pediatric oncology community, leading to treat uniformly most cases of H3 K27-altered diffuse midline gliomas (DMG), based on the simplification that the mutation overrides the histological, radiological, and clinical characteristics of such tumors. Indeed multiple studies described pediatric H3 K27-altered DMG as incurable tumors. But in biology, and in clinical practice, exceptions are frequent, and complexity is the rule. First of all, H3 K27 mutations were found also in non-diffuse gliomas. On the other hand, a minority of DMGs are H3 K27 wild-type, but have a similarly poor prognosis. Furthermore, adult-type tumors may rarely occur in children, and differences in prognosis have emerged between adult and pediatric H3 K27-altered DMG. Tumor location, as well, can determine differences in the outcome: patients with thalamic and spinal DMG have a significantly better survival. Finally, it has been showed that other concomitant molecular alterations may influence the prognosis in H3 K27 gliomas. So, when such additional mutations are found, which one should we be focused on, in order to take the correct clinical decision? Our review of the current literature on pediatric diffuse midline H3 K27-altered DMG tries to address such questions. Indeed, H3 K27 status has become a fundamental supplement to histological grading of pediatric gliomas; however, it might not be sufficient, alone, to exhaustively define the complex biological behavior of DMG in children, and might not represent an indication to a unique treatment strategy across all patients irrespective of age, additional molecular alterations and tumor location.